2012
DOI: 10.1136/gutjnl-2011-300781
|View full text |Cite
|
Sign up to set email alerts
|

HDGF-related protein-3 is required for anchorage-independent survival and chemoresistance in hepatocellular carcinomas

Abstract: These findings indicate that HRP-3 plays an essential role in HCC pathogenesis and suggest that it may serve as a novel prognostic marker and molecular target for development of drugs for treatment of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 33 publications
(30 reference statements)
0
28
0
Order By: Relevance
“…Based on several in vitro trials involving recombinant proteins (30) and the results of preliminary experiments, the HE4 original solution was diluted 250-fold (1 µg/ml), 1,250-fold (0.2 µg/ml) and 3,000-fold (0.083 µg/ml), respectively, for follow-up experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Based on several in vitro trials involving recombinant proteins (30) and the results of preliminary experiments, the HE4 original solution was diluted 250-fold (1 µg/ml), 1,250-fold (0.2 µg/ml) and 3,000-fold (0.083 µg/ml), respectively, for follow-up experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies also showed another HRPs member, HRP-3 was highly upregulated in HCC tissues. HRP-3 can promote anchorage-dependent and -independent growth of HCC cells in vitro and xenograft tumor growth in vivo, possibly through activating the MAPK-ERK pathway [8]. In contrast to HDGF (~240aa) or HRP-3 (~212aa), HRP-2 encodes a larger protein (~671aa), and has not been characterized in previous studies.…”
Section: Introductionmentioning
confidence: 97%
“…For example, HRP-3 is involved in neuritogenesis of primary cortical neurons through modulation of the neuronal cytoskeleton by interacting with tubulin [8] or heparin sulfate proteoglycans [9]. One recent study has reported an association of HRP-3 with cancer [10]. The authors of this study suggested that HRP-3 plays an essential role in the pathogenesis of HCC based on the significant upregulation of HRP-3 in human HCC tissues compared to noncancerous tissues.…”
Section: Introductionmentioning
confidence: 79%